Peran Gaya Mengajar Guru PAI Dalam Membentuk Karakter Religius Siswa - Riko Winata, Cahyariko; Nur Atika, Faizah (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Islamic Religious Education (PAI) plays a strategic role in shaping students' religious character, especially at the junior high school level. Teachers' teaching styles are a crucial factor influencing the success of Islamic Religious Education learning. This study aims to determine the role of Islamic Religious Education teachers' teaching styles in shaping students' religious character at SMP Negeri 1 Karanglewas Banyumas. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included Islamic Religious Education teachers and students. The results showed that Islamic Religious Education teachers' teaching styles played a significant role in shaping students' religious character. Teachers implemented classical, interactional, personalized, and technological styles, and used lectures, discussions, presentations, assignments, digital media, and worship habituation methods. Interactive and communicative approaches have proven effective in increasing students' learning motivation, religious understanding, and positive behavior. Supporting factors include school facilities, religious value-based policies, and family involvement. Inhibiting factors include minimal student involvement in religious activities, a less supportive environment, and limited religious understanding. This study contributes to the development of Islamic Religious Education teachers' teaching styles in order to improve the quality of religious education and the formation of students' religious character.